Lie. skeiris ‘našlys’? - Buivydienė, Rūta (Baltistica, 2000)
LITH. skeiris ‘WIDOWER’?A textological analysis of the 19th century manuscript Litvanica czyli Wiadomośći o Litwie zebrane przez... Ambrożego Kossarzewskiego (the author A. Kašarauskas, who signed in Polish as Kossarzewski) shows that the form skeiris ‘widower’, listed in the multi-volume Dictionary of the Lithuanian Language (LKŽ XII 790) with a reference only to this manuscript, actually does not exist: it is a pseudo-form due to a misreading of the word šeiris ‘widower’ on p. 148 of the aforesaid manuscript. The term for widower šeĩris (šeirỹs) is a form encountered in Old Lithuanian writings, the dialects of West Lithuania, and in Lithuanian folklore (it is noteworthly that Kašarauskas, who collected Lithuanian folklore, is also a native of Samogitia, i. e. of West Lithuania). The author of this article discusses the origin of the word šeĩris (šeirỹs) ‘widower’ in her study of Affinity Terms of the Lithuanian Language: Rūta Buivydienė, Lietuvių kalbos vedybų giminystės pavadinimai (antras pataisytas leidimas), Vilnius, 1997.
Keywords: lietuvių kalba; etimologija; skeiris